An update on Hepatitis B virus - Nath Maity, Soumendra; Kumar, S. S.; Vijayaraghavan, R.; Polavarapu, Rathnagiri (International Research in Medical and Health Sciences, 2018)
Hepatitis B virus (HBV) can cause life-threatening liver infection such as liver cirrhosis and hepatocellular carcinoma. In 1963, Blumberg reported 1st time about the new viral antigen from a blood sample of an Australian aborigine and named as “Australian antigen,” and later this introduced as hepatitis B surface antigen protein of HBV. Approximately 257 million individuals are infected with HBV infection worldwide, and millions of death occurred annually. The virus can spread through sexual contact and parenteral and perinatal routes. HBV causes liver-associated diseases; it can be acute or chronic and symptomatic or asymptomatic disease. The current review provides a detailed account of HBV, its pathogenesis, diagnosis, and treatment.